Effect by adding Ce and In to Mg–6Al Alloy as anode on performance of Mg-air batteries. (29th March 2019) - Li, Yaqiong; Ma, Jingling; Wang, Guangxin; Ren, Fengzhang; Zhu, Yujie; Song, Yongfa; Zhang, Jingli
Abstract: In order to improve discharge activity and utilization of anode material for Mg-air batteries, four anode materials are prepared. The electrochemical performances of these anodes are evaluated by electrochemical impedance spectroscopy and polarization curves. The discharge performances of Mg-air batteries are studied by a constant current discharge test. The results show that the discharge activity of magnesium alloy is improved remarkably with the addition of indium. The corrosion potentials of Mg–6Al–1In and Mg–6Al–1In–1Ce" can reach −1.573 V and −1.600 V respectively. The addition of cerium can reduce the rate of self-corrosion of anode. The corrosion current is only 2.196 × 10 −6 mA·cm −2 . The air batteries with Mg–6Al–1In as the anode have the highest discharge potential at applied current densities of 5, 10, 15 and 20 mA·cm −2 . The anode utilization of an air battery with Mg–6Al–1In–1Ce as the anode can reach 48.5% at an applied current density of 20 mA · cm −2 for 300 min.